2023
DOI: 10.1101/2023.04.21.23288948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A generalizable functional connectivity signature characterizes brain dysfunction and links to rTMS treatment response in cocaine use disorder

Abstract: Cocaine use disorder (CUD) is a prevalent substance abuse disorder, and repetitive transcranial magnetic stimulation (rTMS) has shown potential in reducing cocaine cravings. However, a robust and replicable biomarker for CUD phenotyping is lacking, and the association between CUD brain phenotypes and treatment response remains unclear. Our study successfully establish a corss-validated functional connectivity signature for accurate CUD phenotyping, using resting-state functional magnetic resonance imaging from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…We used ACC seed-based connectivity for VAS prediction. Multiple studies have consistently reported the structural and functional changes in this region in CUD 45,46 and also its relationship with VAS 47 . Results showed that the connectivity of ACC with precentral gyrus, occipital cortex, and pre/post-central gyrus predicted greater reduction in VAS for 2w, 3m, and 6m after rTMS application, respectively.…”
Section: A Sbc Resultsmentioning
confidence: 98%
“…We used ACC seed-based connectivity for VAS prediction. Multiple studies have consistently reported the structural and functional changes in this region in CUD 45,46 and also its relationship with VAS 47 . Results showed that the connectivity of ACC with precentral gyrus, occipital cortex, and pre/post-central gyrus predicted greater reduction in VAS for 2w, 3m, and 6m after rTMS application, respectively.…”
Section: A Sbc Resultsmentioning
confidence: 98%
“…A participants checklist with the specific MRI sequences acquired can be found in supplementary material. To date, the present dataset has been used to examine the short and long-term clinical benefits of rTMS and their impact on functional connectivity 10 , to identify cognitive deficits of CUD participants by machine learning algorithms 11 , to improve diffusion MRI segmentation methods using deep learning 12 , to predict clinical outcomes using microstructural changes 13 , and to identify a generalizable functional connectivity signature characterizes brain dysfunction in cocaine use disorder 14 . Altogether, this dataset could serve for the study of the longitudinal impact of rTMS as a promising add-on treatment for CUD, as well as to test new neuroimaging algorithms and analysis techniques.…”
Section: Background and Summarymentioning
confidence: 99%
“…Its content focuses on the behavior of depression, with vegetative, cognitive, and anxiety symptoms having the greatest weight in the total calculation of the scale. The cutoff points to define severity are no depression (0-7); mild depression (8)(9)(10)(11)(12)(13)(14)(15)(16); moderate depression (17)(18)(19)(20)(21)(22)(23); and severe depression (≥24) 40 .…”
Section: Hamilton Depression Rating Scale (Hdrs)mentioning
confidence: 99%